2005
DOI: 10.1080/13561820500165167
|View full text |Cite
|
Sign up to set email alerts
|

Professional perceptions of joint working in primary care and social care services for older people in Scotland

Abstract: The purpose of this paper is to report health and social care professionals' perceptions on joint working for the care of older people in Scotland. Semi-structured interviews were conducted with 34 primary care and social care professionals. These professionals emphasised that joint working requires a fundamental change in thinking and a scrutiny of professional roles and identities and is influenced by the given geographical and organisational infrastructure. In order to facilitate sustained joint working kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 16 publications
2
41
0
Order By: Relevance
“…Some studies point to the fact that co-location is a necessary prerequisite for integrated care [363738]. A recent study found that co-location of multiple disciplines within a primary care practice was associated with increased capacity to provide broad, specialised and preventive care for people with chronic disease [39 p. 5].…”
Section: Theory and Methodsmentioning
confidence: 99%
“…Some studies point to the fact that co-location is a necessary prerequisite for integrated care [363738]. A recent study found that co-location of multiple disciplines within a primary care practice was associated with increased capacity to provide broad, specialised and preventive care for people with chronic disease [39 p. 5].…”
Section: Theory and Methodsmentioning
confidence: 99%
“…In a discussion of professional perspectives on working together, Hubbard and Themessl-Huber (2005) highlight that that joint working is not just about transferring information, but about creating new thinking. They argue that there is a need to focus attention on "how knowledge is created rather than upon how knowledge is exchanged".…”
mentioning
confidence: 99%
“…Further work is required to explore the impact of SAP on outcomes for service users and carers as well as in more diverse populations. The effect that improving joint working will have on outcomes for older people and their informal carers also requires study (Hubbard and Themessl-Huber 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Partnership working is a central theme of the current UK Government"s "Third Way" policies (Hudson 2002) and aims to blur boundaries in order to provide seamless care across health and social care to patients (Hubbard and Themessl-Huber 2005). However, overcoming the barriers to joint working have been likened to demolishing the Berlin Wall .…”
mentioning
confidence: 99%